Pendekatan Pendidikan Matematika Realistik Indonesia Berbantuan Puzzle Tangram untuk Mengajarakan Luas Bangun Datar Gabungan - Palupi, Evangelista Lus Windyana (Jurnal Elemen, 2017)
This study aims to design a learning activity to help student learn the concept of area of complex figures. Realistic mathematics approach is used as learning approach with the helps of tangram as manipulative. Design research is employed as research method. The activity is designed based on the result of curriculum analysis and studentsâ needs. Then, the designed activity is implemented and tested in a real class of Grade 6. Thirty-two students are involved in this research. Analysis retrospective is done in order to know how the designed activity help the students. The results indicate that the designed activity can be used as an alternative to teach students in determining the area of complex figures.